HIV Stigma and Mental Health Outcomes Among the Youth Living With HIV in Mukono District - Samuel Muyonga (Uganda Christian University, 2025)
This study explores the impact of HIV-related stigma on the mental health outcomes of youth living with HIV in Mukono District, Uganda. Through focus group discussions with youth, key informants, and healthcare providers, the research identifies critical themes such as selfstigma and internalized stigma, social isolation and peer stigma, the role of health providers, and the importance of peer support and counselling. The findings reveal that self-stigma and internalized stigma significantly affect the mental health of youth, leading to feelings of shame, loss of self-esteem, and social withdrawal. Social isolation and peer stigma further exacerbate these challenges, with negative attitudes from peers and the broader community reinforcing feelings of loneliness and stress. Health providers play a crucial role in offering emotional and practical support, though concerns about confidentiality breaches highlight the need for strict privacy protocols. Peer support and counselling emerge as vital components in mitigating the effects of stigma, providing emotional strength, and promoting adherence to treatment. The study concludes with recommendations for enhancing community education, strengthening confidentiality protocols, expanding peer support programs, improving practical support measures, and facilitating safe disclosure practices. These interventions are essential for improving the well-being and quality of life for youth living with HIV in Mukono District.
Undergraduate research